Forêt identitaire, forêt partagée : Trajectoire d’une recherche participative chez les Anicinapek de Kitcisakik (Québec, Canada) - Marie Saint-Arnaud; Lucie Sauvé; Daniel Kneeshaw (VertigO)
Developing forest management strategies adapted to Aboriginal cultures figures among the challenges of modern forestry in Canada. The Anicinapek of Kitcisakik (Quebec, Canada) have chosen to engage in a process of research, in collaboration with an interdisciplinary university team and a regrouping of industrial partners. This initiative made it possible to undertake an intercultural dialogue with the goal of better defining the basis of an “Aboriginal forestry” based on a process of identification of local criteria and indicators for assessing and improving forest management scenarios. The path taken for this collaborative research is presented as well as the main educational, methodological and strategic challenges which arose in the process.